Association Aamong Ppolymorphisms in the Aapoptosis‐Rrelated NKX3‐1, Caspase‐3, Caspase‐9, and BCL‐2 Genes and Prostate Cancer Susceptibility From 9706 Cases and 12,567 Controls - Yanyan Feng; Zhenting Feng; Dan Li; Jiandong Gui; Zhihong Song; Xiaohua Xie; Lijie Zhu; Yuanyuan Mi (Cancer Reports)
ABSTRACT Background While there is a growing volume of evidence suggesting that relatively prevalent functional polymorphisms present within apoptosis‐related genes may influence human prostate cancer (PCa) susceptibility, the clinical relevance of these findings remains inconclusive. Aims This meta‐analysis was thus developed with the goal of generating more precise estimates of the relationships between polymorphisms in four apoptosis‐associated genes (NKX3‐1, caspase‐3, caspase‐9, and BCL‐2) and the risk of PCa. Methods and Results The PubMed, Web of Science, Google Scholar, Embase, Cochrane Library, and SinoMed (CNKI and Wanfang) databases were searched for relevant studies published through December 20, 2023, using the following keywords: “polymorphism” or “variant” and “carcinoma” or “cancer” or “tumor” and “NKX3‐1,” “CASP3” or “Caspase‐3,” “CASP9” or “Caspase‐9,” “BCL‐2” or “B‐cell lymphoma” and “prostate cancer” or “PCa” or “prostate adenocarcinoma.” This approach led to the identification of 22 case–control studies related to the association between apoptosis‐related gene polymorphisms and PCa susceptibility enrolling 9706 cases and 12 567 controls. Subsequent analyses revealed that the NKX3‐1 rs2228013, CASP9 rs1052571, and CASP9 rs4645982 polymorphisms were associated with greater PCa risk, whereas the CASP3 rs4647603 polymorphism was associated with a risk reduction. Conclusion These findings provide strong evidence for the potential contributions of polymorphisms in the apoptosis‐related caspase‐3, caspase‐9, and NKX3‐1 genes in the onset and progression of PCa.